Genome-Wide Identification of AP2/ERF Transcription Factors in Cauliflower and Expression Profiling of the ERF Family under Salt and Drought Stresses - Li, Hui; Wang, Yu; Wu, Mei; Li, Lihong; Li, Cong; Han, Zhanpin; Yuan, Jiye; Chen, Chengbin; Song, Wenqin; Wang, Chunguo (Frontiers in Plant Science, 2017)
The AP2/ERF transcription factors (TFs) comprise one of the largest gene superfamilies in plants. These TFs perform vital roles in plant growth, development, and responses to biotic and abiotic stresses. In this study, 171 AP2/ERF TFs were identified in cauliflower (Brassica oleracea L. var. botrytis), one of the most important horticultural crops in Brassica. Among these TFs, 15, 9, and 1 TFs were classified into the AP2, RVA, and Soloist family, respectively. The other 146 TFs belong to ERF families, which were further divided into the ERF and DREB subfamilies. The ERF subfamily contained 103 TFs, while the DREB subfamily contained 43 TFs. Phylogenetic analysis results indicated that the AP2/ERF TFs can be classified into 13 groups, in which 25 conserved motifs were confirmed. Some motifs were group- or subgroup- specific, implying that they are significant to the functions of the AP2/ERF TFs of these clades. In addition, 35 AP2/ERF TFs from the 13 groups were selected randomly and then used for expression pattern analysis under salt and drought stresses. The majority of these AP2/ERF TFs exhibited positive responses to these stress conditions. In specific, Bra-botrytis-ERF054a, Bra-botrytis-ERF056, and Bra-botrytis-CRF2a demonstrated rapid responses. By contrast, six AP2/ERF TFs were showed to delay responses to both stresses. The AP2/ERF TFs exhibiting specific expression patterns under salt or drought stresses were also confirmed. Further functional analysis indicated that ectopic overexpression of Bra-botrytis-ERF056 could increase tolerance to both salt and drought treatments. These findings provide new insights into the AP2/ERF TFs present in cauliflower, and offer candidate AP2/ERF TFs for further studies on their roles in salt and drought stress tolerance.